(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2022)
Additive Manufacturing (AM) is rapidly gaining acceptance in healthcare. Due to 3D printing of polyetheretherketone (PEEK) constructions almost any complex geometry, e. g. bio-mimicking implants or light-weight hollow implant bodies, can be produced. In this paper a direct comparison between PEEK and titanium osteosynthesis plates is achieved with a finite element analysis. By that, pros and cons of PEEK as implant material are discussed and different use cases are identified. For the comparison a generic osteosynthesis plate for diaphysis is designed. The exceeding of the yield strength even at low bending and torsional loads highlights the problems that occur when applying PEEK implants at locations which are affected by moderate mechanical loads. Since fracture stabilisation is the main function of osteosynthesis plates, stiffness is a highly relevant property of these. Therefore, a direct exchange of titanium to PEEK would increase the risk of non-union. Thus, a different structure or an improved material, e. g. carbon fibre PEEK composite, is required for loaded locations to replace metallic implants.